Identification of field pea gene bank samples by component characteristics in relation to the breeding of plant varieties of various directions of economical use - В. В. Чернуський (Plant Varieties Studying and Protection)
Assumption is made that identification of valuable genotypes is possible in specific stability points of phase-parametric systems, that is, when the effect of dynamism acquires gradient and discrete anisotropic composition by way of converting the phenotype variability in the temporal and parametric and characteristic specific vector-spaced system. Devices have been suggested (electronic board for the characteristics spectral expression, 3D configuration of a characteristic variation series) for displaying the location sample parametric pool in the general statistic range of quantitative characteristics. A characteristic has been detected (number of seeds in a pod) that carry the traits inherent in pseudo-qualitative and oligogenic characteristic. According to findings of the study, characteristics are identified that conform to various directions of economical use